Synapseudes marinae (Tanaidacea, Apseudomorpha, Metapseudidae) the first metapseudid species from the Sea of Crete, and redescription of S. mediterraneus from Israel - Maxim-J. Bâlcu; Rozalia M. Motoc; Andrei Ștefan; Dumitru Murariu; Oana P. Popa (Zoosystematics and Evolution)
We present the morphological and genetic characterization of a new shallow-water tanaid, Synapseudes marinae sp. nov., collected from Milatos Beach on the northern coast of Crete, marking the first record of the genus Synapseudes from the Sea of Crete. This species exhibits strong morphological similarities to Synapseudes mediterraneus, briefly described by Băcescu in 1977 from the Mediterranean waters of Israel, which is also redescribed herein. In addition to the taxonomic descriptions, we include mitochondrial cytochrome c oxidase subunit I (COI) data to support the classification of the newly described species within the Synapseudes genus, noting a p-distance value of 28% between species of Synapseudes. A detailed diagnosis of the Synapseudes species occurring in the Mediterranean Sea is provided. Scanning electron microscopy images of S. marinae sp. nov. have been incorporated to enhance the optical microscope drawings and provide a more comprehensive depiction of this new species.